Coherent integration in compressed sensing radar - Xia, Yali (2013)
The resolution of Radar is known to be limited by the radar uncertainty principle. Compressed Sensing which is a novel algorithm has exhibited great potential in radar detection because of its prime advantage of better resolution. However, the application of compressed sensing to Radar is very abstract and real-time issues need to be introduced. Returned signal of radar usually comes with heavy noise and compressed sensing fails under such condition. Coherent integration is widely employed to increase the SNR through Doppler processing in Pulse-Doppler Radar nowadays. This report describes how coherent integration contributes to the improvement of SNR of the signal and further analyse the performance of coherent integration of compressed sensing in radar when Basis Pursuit is used in the signal reconstruction.